Boosting the Decision-Making in Smart Ports by Using Blockchain - Durán, Claudia A.; Fernández Campusano, Christian.; Carrasco Armijo, Raúl Vicente.; Vargas, Manuel; Navarrete, Alejandro (Institute of Electrical and Electronics Engineers Inc., 2021)
Blockchain technology (BC) offers an innovation platform for decentralized and transparent transactions in the maritime port industry. This technology allows guaranteeing trust, transparency and traceability of cargo and data to be tracked. Today, in the port systems of emerging market countries, BC technology is increasingly being incorporated into information and communication processes. In parallel, the social domain has begun to be explored due to the lack of link between the port and the city it occupies, and the need to incorporate public actors in decision-making at the governance level. In this sense, the present work aims to promote BC technology in order to transform data and information into useful knowledge for effective decision making, through the use of Crowdsourcing. A Crowdsourcing Blockchain CrowdBC conceptual framework and its architecture are generated for a port system in which the cyber-technological, social and cognitive domains (CSTC) of smart ports, the knowledge generation process and Crowdsourcing technology are interrelated. Finally, opportunities are discussed for ports that are in permanent development to reduce the gaps with the smart industry. As a discussion, two possible scenarios and recommendations for future implementations that consider the social and cognitive aspects of Industry 4.0 are presented.
Keywords: Cybernetic-social-technological-cognitive model.; Smart port.; Crowdsourcing.; Blockchain.